PKM Pembelajaran Sains Fisika dengan Metode Eksperimen Disertai Lembar Kerja Siswa (Lkpd) Untuk MGMP IPA Guru di Kabupaten Maros - Muhammad Arsyad; Helmi Helmi; Jasruddin Malago (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. Community Partnership Program (PKM) has been conducted with the aim of 1) designing physics science learning with experimental methods accompanied by LKPD, 2) designing the use of Student Worksheets (LKPD) in physics science learning, 3) analyzing the responses of Physics Science Teachers in the implementation of PKM Activities. several methods were used to achieve the goal; 1) lecturing method, 2) training method, 3) experimentation method, 4) assigning tasks method, 5) discussion method, 6) problem solving method. The results obtained from this PKM activity are; 1) Physical Science Learning Plan with experimental method accompanied by Student Worksheet (LKPD), 2) Use of Learner Worksheet (LKPD) where 93.93%, participants agree to design, 90.90% of participants agree to conduct experiments and compose, 75.76% of participants will disseminate activities for other subjects, 81.82% of participants will assign tasks to Students by conducting observations, 98.92% of participants will make PKM a regular MGMP activity every year, 93.93% of Teachers are able to carry out what is obtained in the Training , 3) The Responses of Physics Science Teachers in the Implementation of PKM Activities, 98.92% said the activities in accordance with the expectations and objectives of teachers participating in PKM activities, 45.45% said, Learning Science Physics with the method of experimentation accompanied (LKPD) takes longer in the preparation, 60.61% were able to design Physics Science Learning with experimental methods accompanied by Student Worksheet (LKPD) with a combination of KIT IPA, 98.92% said that Learning Science Physics with experimental methods accompanied by Student Worksheet (LKPD) as a learning resource requires special training and skills.